2008
DOI: 10.1002/jso.21195
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous melanoma in Asian‐Americans

Abstract: This is the largest study to date on melanoma in AsA. Compared to NHW, AsA are more likely to have acral lentinginous tumors, thick tumors, and higher stage. Despite this, their survival is similar to the NHW population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 38 publications
1
33
1
Order By: Relevance
“…10 Over the past 15 years, an increasing incidence of invasive ALM among Hispanics has also been documented. 11 Lack of awareness of melanoma in those with ethnic skin and prevalence in anatomical sites that are often not inspected by physicians may contribute to presentation at advanced stages of the disease.…”
mentioning
confidence: 99%
“…10 Over the past 15 years, an increasing incidence of invasive ALM among Hispanics has also been documented. 11 Lack of awareness of melanoma in those with ethnic skin and prevalence in anatomical sites that are often not inspected by physicians may contribute to presentation at advanced stages of the disease.…”
mentioning
confidence: 99%
“…Based on data from the National Cancer Data Base, Shin et al reported that Asian-Americans represented 1237 of the 483 050 cutaneous melanoma diagnoses between 1986 and 2005, clearly suggesting an under-representation of these patients compared to the general population 2. Interestingly, Asian patients were more likely to have acral lentiginous melanoma, and to present with higher tumour stage compared to white patients, further suggesting a unique biology for these patients compared to Caucasians 2…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Hispanics, blacks, and Asians are more likely to present with late-stage melanoma (regardless of subtype) at the time of diagnosis. 34 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…12 Lee et al found greater delays in diagnosis among Asian patients with ALM 13 , and other studies have demonstrated thicker lesions at diagnosis in ethnic minorities. 4,9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation